RESILIENSI PADA LANJUT USIA PEREMPUAN YANG DITINGGAL MATI PASANGAN HIDUPNYA DI DESA MARGOMULYO KECAMATAN GLENMORE BANYUWANGI - Nasihatus Solehati; Muhammad Muhib Alwi (Sociocouns: Journal of Islamic Guidance and Counseling, 2021)
Old age is the last step in the human development period. During this period humans will experience seatbacks and changes in their lives. Especially, when they are lose the spouses. Lost spouses make the older experience the deep wound and feel saddened by what happened to them, specifically happen to women old. The women old will experience role changes without their spouse because she will live and fulfill their needs without their husband. Then, they need resilience to build a power the women old who live without their spouse to be able to survive in dealing with their problems. The purpose of this research to know the resilience from the women old who live without their husband and to know the supporting and blocker factors in process of resilience to the women old whom live in Margomulyo village. This research used qualitative descriptive with the kind of research is Case Study. The data were gathered by observation, interview, and document review. Data analysis used data reduction, data presentation, and concluding the data. The result of this research was five subjects of this research have good resilience. It can be known by the women old condition who can control their sad emotion, desire, work spirit, try sincerely, able to positive thinking and caring attitude to another, believing in herself to solve the problems, able to increase the positive aspects in herself. The supporting factors resilience from women olds were spiritual and social factors. The blocker factors from the women old were social and economic factors.